How Social Philosophy is Possible: the Transition from Postmodern to Metamodern - K. V. Arshin (Дискурс)
Introduction. The establishment of the dominance of postmodernism as a key paradigm of philosophical knowledge raised the question of the subject of social philosophy as a philosophical discipline that studies the problems of sociality in relation to a person. On the one hand, this led to a crisis in the social sciences, since social philosophy lost its status as a metascience in the structure of social knowledge. On the other hand, it expanded the subject field of social philosophy, including in it objects to which the interest of social philosophers had never been directed (inanimate objects, animals).   Methodology and sources. The basis of the methodology of the work is the methods of critical analysis and comparative studies, which allows us to describe the logic of the development of the problem of the loss of the unity of its subject by social philosophy within the framework of events of both real and intellectual history.   Results and discussion. The article makes an attempt to describe possible transformations of the thematic field of social philosophy in the process of transition from postmodernity to metamodernity. The author, analyzing the recognized problem of modern social philosophy (its fragmentation, the absence of an object of study), demonstrates the possibility of its defragmentation during the metamodern period when research interest is turned to such issues as the study of man as a social being, the influence of new technologies on the transformation of man and the social, the rethinking of the social in the explosive development of technology, and finally, the study of the dialectics of social emotions on society and man.   Conclusion. The author comes to the conclusion that in its current state, fragmented social philosophy is not ready for subject reorientation, which means the need for qualitative changes in the subject of social philosophy.